The Impact of Covid-19 Pandemic on Customer Satisfaction and Business Performance of Foodpanda - Daisy Mui Hung Kee; Siti Nur Sharipah Zakiah; Anis Nadhirah; Norini Binti Shamsuri; Noor Anis Syazana; Nur Izatul Nadia (Advances in Global Economics and Business Journal, 2021)
The paper aims to examine the impact of the COVID-19 pandemic on customer satisfaction and business performance of Foodpanda. The number of COVID-19 cases worldwide continues to rise, and this pandemic has impacted many companies' business performance. A total of 100 Food Panda customers were surveyed. The findings demonstrate that the business performance of Food Panda increases during the outbreak of the Covid-19. The findings also indicate that customers are satisfied with the service quality provided by Foodpanda. Customer satisfaction is strongly linked to business performance. The discussion and recommendations are presented.